2014
DOI: 10.5815/ijmecs.2014.09.03
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Teaching Computer Programming: first year students’ perspective

Abstract: The teaching of computer programming is one of the greatest challenges that have remained for years in Computer Science Education. A particular case is computer programming course for the beginners. While the traditional objectivist lecture-based approaches do not actively engage students to achieve their learning outcome, we believe that integrating some cutting-edge processes and practices like agile method into the teaching approaches will be leverage. Agile software development has gained widespread popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
(24 reference statements)
1
24
0
1
Order By: Relevance
“…This assertion agrees with [16] who purposed equipping of computer classrooms for improved effective understanding and achievement of learning goals.  Teachers should be encouraged to utilize computers in their teaching and learning process because goes a long way to enhance the process and enable teachers to perform their duties effectively, and efficiently.…”
Section: Recommendationssupporting
confidence: 80%
“…This assertion agrees with [16] who purposed equipping of computer classrooms for improved effective understanding and achievement of learning goals.  Teachers should be encouraged to utilize computers in their teaching and learning process because goes a long way to enhance the process and enable teachers to perform their duties effectively, and efficiently.…”
Section: Recommendationssupporting
confidence: 80%
“…Despite the power of computer-based learning, research by Chou and colleagues has shown the importance of face-to-face teaching, and the importance of evaluating combinations of learning methods [10]. There are also numerous studies on the commuter-based learning for computing areas such as open source [11], computer programming [12], web learning [13] and so forth. Much research has been conducted on different forms of web-based learning such as e-learning [14], and effectiveness of MOODLE [15].…”
Section: Related Work In Mindfulness Traningmentioning
confidence: 99%
“…So, teachers are always looking for effective teaching methods to enhance student motivation, problem solving and metacognitive skills in learning programming. Notably, there has been much research done on how to teach programming courses in interesting and effective ways to novices [14,18,19,20,21,22]. However, those proponents accepted that "formal lectures are not a useful way of teaching programming" [10,23].…”
Section: Introductionmentioning
confidence: 99%